Enhanced passive surveillance of influenza vaccination in England, 2016−2017- an observational study using an adverse events reporting card - Simon de Lusignan; Filipa Ferreira; Silvia Damaso; Rachel Byford; Sameera Pathirannehelage; Anne Yeakey; Ivelina Yonova; Anne Schuind; Gael Dos Santos (Taylor & Francis Group, 2019)
Influenza is a major public health burden, mainly prevented by vaccination. Recommendations on influenza vaccine composition are updated annually and constant benefit-risk monitoring is therefore needed. We conducted near-real-time enhanced passive surveillance (EPS) for the influenza vaccine, Fluarix Tetra, according to European Medicines Agency guidance, in 10 volunteer general practices in England using Fluarix Tetra as their principal influenza vaccine brand, from 1-Sep to 30-Nov-2016. The EPS method used a combination of routinely collected data from electronic health records (EHR) and a customized adverse events reporting card (AERC) distributed to participants vaccinated with Fluarix Tetra. For participants vaccinated with a different influenza vaccine, data were derived exclusively from the EHR. We reported weekly and cumulative incidence of pre-defined adverse events of interest (AEI) occurring within 7 days post-vaccination, adjusted for clustering effect. Of the 97,754 eligible participants, 19,334 (19.8%) received influenza vaccination, of whom 13,861 (71.7%) received Fluarix Tetra. A total of 1,049 participants receiving Fluarix Tetra reported AEIs; 703 (67%) used the AERC (adjusted cumulative incidence rate 4.96% [95% CI: 3.92−6.25]). Analysis by individual pre-specified AEI categories identified no safety signal for Fluarix Tetra. A total of 62 individuals reported an AEI with a known brand of non-GSK influenza vaccine and 54 with an unknown brand (adjusted cumulative incidence rate 2.59% [1.93−3.47] and 1.77% [1.42−2.20], respectively). In conclusion, the study identified no safety signal for Fluarix Tetra and showed that the AERC was a useful tool that complemented routine pharmacovigilance by allowing more comprehensive capture of AEIs.10.1080/21645515.2019.1565258-UF0001